Non-economic loss and damage in the context of climate change: understanding the challenges - Olivia Serdeczny; Eleanor Waters; Sander Chan (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
The concept of non-economic loss and damage (NELD) captures the impacts of climate change that are hard to quantify and often go unnoticed by the outside world, such as the loss of traditional ways of living, cultural heritage and biodiversity. It also encapsulates losses whose valuation raises ethical concerns – loss of life and human health. The concept of NELD has recently emerged as a policy issue in the negotiations under the United Nations Framework Convention on Climate Change. The goal is to implement or develop approaches that minimise the risk of NELD occurring or that effectively respond to losses. This paper is the first to propose the distinctions between approaches to avoid NELD and approaches responding to unavoidable NELD. It provides a conceptual framework in which the highly diverse cases of NELD can be categorised. It identifies the main characteristics of NELD items and their associated challenges for policy-making. Building on this conceptual approach, the paper sketches an ideal international policy framework that addresses NELD and provides policy recommendations at the national level.
Keywords: 330; Klimawandel